1991
DOI: 10.1037/0021-9010.76.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Group decision making under stress.

Abstract: Understanding the processes by which task groups function is a major concern of social psychologists who study small groups. Equally important to the applied group researcher is the understanding of how group processes are altered by the external environment. Research suggests that organizations respond to stress with a centralization of authority so that decision making becomes concentrated in the higher levels of an organizational hierarchy. In this study, this hypothesis was extended to the small-group leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
0
5

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(150 citation statements)
references
References 36 publications
2
143
0
5
Order By: Relevance
“…[4][5][6][7][8][15][16][17] The current evidence in surgical disciplines suggests that MP is a safe and cost-effective method for training novice surgeons in technical procedures. 8,16,17 A randomized controlled trial by Arora et al found MP to be beneficial for enhancing the imagery and performance of novice surgeons during a simulated laparoscopic cholecystectomy. 5,8 Recently, Hayter et al found that warm-up using MP did not improve anesthesia CRM skills in novice anesthesia trainees during a simulated cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][15][16][17] The current evidence in surgical disciplines suggests that MP is a safe and cost-effective method for training novice surgeons in technical procedures. 8,16,17 A randomized controlled trial by Arora et al found MP to be beneficial for enhancing the imagery and performance of novice surgeons during a simulated laparoscopic cholecystectomy. 5,8 Recently, Hayter et al found that warm-up using MP did not improve anesthesia CRM skills in novice anesthesia trainees during a simulated cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…As modern weapon systems push the technology envelope and military focus shifts toward the crisis and limited objective warfare (CALOW) environment, team members are often placed in precarious positions requiring the rapid processing and synthesis of vast amounts of data before decisions can be reached (Coovert, Cannon-Bowers, & Salas, 1990;Driskell & Salas, 1991a, 1991b.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, time pressure can present a different type of uncertainty for the organization. When time resources are few and normal communication is stressful, organizations will experience greater constraint on their decision making processes, which will ultimately affect the organizationÕs ability to combat the occurrence of mistakes [22]. This is especially true of todayÕs world in which organizations have to respond to the environment in a timely manner in order to stay competitive [23].…”
Section: Time Resourcementioning
confidence: 99%